2021
DOI: 10.1101/2021.04.02.21253083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Site performance of AI software for stroke detection and Triage

Abstract: Background: Recently developed software utilizing artificial intelligence for fast detection and triage of stroke cases has the potential to accelerate stroke care and improve patient outcomes. We performed this analysis to evaluate the performance and time to notification of one such software RAPID LVO. Methods: We created a consecutive database of 151 patients for whom scans were processed by the software over a period of eight months. The outputs and running times of the software were collected, alongside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…One limitation of this study is that we did not evaluate the impact of these tools on clinical outcomes. Other studies have previously shown a significant improvement in transfer times of LVO patients ( 10 ), but there are mixed results at comprehensive stroke centers ( 9 , 11 13 ). This study included a relatively small sample size at a single institution which may limit generalizability.…”
Section: Discussionmentioning
confidence: 95%
“…One limitation of this study is that we did not evaluate the impact of these tools on clinical outcomes. Other studies have previously shown a significant improvement in transfer times of LVO patients ( 10 ), but there are mixed results at comprehensive stroke centers ( 9 , 11 13 ). This study included a relatively small sample size at a single institution which may limit generalizability.…”
Section: Discussionmentioning
confidence: 95%
“…Based on the searches and inclusion criteria described above, a total of 30 publications relating to 22 studies [33][34][35][36][39][40][41][43][44][45][46][48][49][50][51][52]55,56,[59][60][61][62] were included in the review; the results section of this report cites studies using the primary publication and, where this is different, the publication in which the referenced data were reported.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…The studies included in this review evaluated AI-derived software technologies produced by iSchemaView, Viz, Brainomix and Avicenna. For iSchemaView, three studies evaluated Rapid CTA, 33,35,36 two studies evaluated Rapid LVO, 41,55 one study evaluated Rapid CTP 50 and two studies assessed the effects of implementing RapidAI (comprising Rapid CTA and Rapid CTP). 34,49 Eight studies evaluated Viz LVO 40,43,45,46,52,[59][60][61] and one study evaluated Viz ICH.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial studies have shown that the implementation of an automated LVO detection tool is associated with reductions in transfer times, door-to-treatment times, and hospital and ICU stays, as well as improvements in clinical outcomes ( 18–20 ). Others have found low-to-moderate sensitivity and specificity and slower time to notification of these tools when implemented in the acute setting ( 21 ).…”
Section: Introductionmentioning
confidence: 99%